Opt-out Testing Pilot for Sexually Transmitted Infections Among Immigrant Detainees at 2 Immigration and Customs Enforcement Health Service Corps–Staffed Detention Facilities, 2018. (July 2020) - Lederman, Edith; Blackwell, Andria; Tomkus, Gina; Rios, Misty; Stephen, Brent; Rivera, Ada; Farabaugh, Philip
Objectives: Correctional settings (prisons, jails, detention facilities) provide a unique opportunity to screen for sexually transmitted infections (STIs) among correctional populations with a high prevalence of infection. Immigrant detainees are a distinct and poorly described correctional population. The main objective of this study was to determine the feasibility of a national STI screening program for immigrant detainees. Methods and Materials: We developed an opt-out STI testing program that included electronic health record integration, patient education, and staff member training. We piloted this program from June 22 through August 19, 2018, at 2 detention facilities with different operational requirements and detainee demographic characteristics. We assessed STI test positivity rates, treatment outcomes, estimated cost to conduct testing and counseling, and staff member perceptions of program value and challenges to implementation. Results: Of 1041 immigrant detainees approached for testing, 526 (50.5%) declined. Of 494 detainees who were tested, 42 (8.5%) tested positive for at least 1 STI; the percentage positivity rates were 6.7% (n = 33) for chlamydia, 0.8% (n = 4) for syphilis, 0.8% (n = 4) for gonorrhea, 0.6% (n = 3) for hepatitis B, and 0.2% (n = 1) for HIV. The estimated cost to detect any STI ranged from 500 to 961; the estimated cost to identify 1 person infected with HIV ranged from 22 497 to 43 244. Forty of 42 persons who tested positive began treatment before release from custody. Medical staff members had positive views of the program but had concerns about workload. Practice Implications: STIs are prevalent among immigrant detainees. A routine screening program is feasible if operational aspects are carefully considered and would provide counseling, education, and treatment for this vulnerable population.